2012
DOI: 10.1051/parasite/2012192129
|View full text |Cite
|
Sign up to set email alerts
|

Digenean species diversity in teleost fishes from the Gulf of Gabes, Tunisia (Western Mediterranean)

Abstract: This study is the first attempt to survey the diversity of fish digeneans in the Gulf of Gabes (southern coast of Tunisia). A total of 779 fishes belonging to 32 species were sampled. 53 species of Digenea belonging to 15 families were recorded. Among these species, 24 are reported for the first time from the coast of Tunisia. We report one new host record, Lecithochirium sp. from Sardinella aurita. The Hemiuridae is the dominant family. A host-parasite list is presented with the information on the prevalence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
5
15
5
Order By: Relevance
“…The poor values of communities in GN suggest an unstable ecosystem with a decrease in the biomass and densities of hosts. In contrast, the higher values of parasite communities found in GS, where samples were obtained close to a marine reserve, could be related to the relative stability of its ecosystem 2,3,[11][12][13] , which shows abundant Posidonia meadows and a more preserved benthonic ecosystem with richer communities of intermediate hosts for digeneans. Regarding the ecto-parasite community, it has been demonstrated that crustaceans and monogeneans are more sensitive than endo-parasites to the environmental deterioration, anthropogenic or other pressures (e.g.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The poor values of communities in GN suggest an unstable ecosystem with a decrease in the biomass and densities of hosts. In contrast, the higher values of parasite communities found in GS, where samples were obtained close to a marine reserve, could be related to the relative stability of its ecosystem 2,3,[11][12][13] , which shows abundant Posidonia meadows and a more preserved benthonic ecosystem with richer communities of intermediate hosts for digeneans. Regarding the ecto-parasite community, it has been demonstrated that crustaceans and monogeneans are more sensitive than endo-parasites to the environmental deterioration, anthropogenic or other pressures (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Metazoan parasites are considered to be sensitive to environmental stress and potential bio-indicators of water quality and environment stability. Their community's descriptors have been considered as effective indicators that reflect habitat alterations and have been used to evaluate the environment health status and anthropogenic impact in coastal habitats [2][3][4][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…The Gulf was recently identified as one of the eleven consensus ecoregions of the Mediterranean and is considered, together with the Venetian shelf region, as a shallow and phytoplankton bloom region (Ayata et al, 2017). Additionally, this area is usually considered an important nursery for several fish species (Hattour et al, 1995;Derbel et al, 2012;Enajjar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in Tunisia, interest in these helminths has been developed only over the past 20 years with the pioneer studies of Gargouri Ben Abdallah and Maamouri (1997, 2002, 2005a, b, 2008) and Gargouri Ben Abdallah et al (2010) on the diversity and the life-cycles of fish digeneans off the northern coast of the country. In 2012, another determined effort was made by Derbel and co-workers to contribute to our knowledge of the digenean fauna in marine fishes off the southeastern coast of Tunisia (Derbel et al, 2012). In an earlier study on the biodiversity of digeneans in the Bizerte Lagoon (an inlet of the Mediterranean in northeastern Tunisia), we reported 30 species of digeneans from sparid fishes (Gargouri Ben Abdallah et al, 2011; Antar & Gargouri, 2013; Antar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%